2018
DOI: 10.1108/jcre-08-2017-0021
|View full text |Cite
|
Sign up to set email alerts
|

A psychoacoustical approach to resolving office noise distraction

Abstract: Purpose -The purpose of this paper is to determine whether noise is affected by psychological factors rather than simply by physical metrics. For example, personality type, age, perceived control and screening ability were explored, as well as the choice of primary workplace.Design/methodology/approach -An online survey was conducted which resulted in 517 valid responses. The survey included the personality profiling along with questions related to noise and personal circumstances. The key noise metrics were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 17 publications
1
33
1
Order By: Relevance
“…While workers perceive taller panels (with adequate sound‐absorbent properties) as a way to reduce noise and visual distractions in this study, psychosocial factors affecting noise and its perception should also be addressed (Oseland & Hodsman, ). The findings also indicate that special consideration should be given to the design of visual fields and lines of movement in traffic patterns (Hong & Yoo, ) that can support workspace orientation and location for privacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While workers perceive taller panels (with adequate sound‐absorbent properties) as a way to reduce noise and visual distractions in this study, psychosocial factors affecting noise and its perception should also be addressed (Oseland & Hodsman, ). The findings also indicate that special consideration should be given to the design of visual fields and lines of movement in traffic patterns (Hong & Yoo, ) that can support workspace orientation and location for privacy.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies document that long‐term reactions to environmental stressors, such as noise caused by acoustical distractions, include decreased performance (Banbury & Berry, ; Cotton & Hart, 2003) and negative health consequences such as chronic fatigue, burnout, and musculoskeletal disorders (Danielsson & Bodin, ; De Lange, Taris, Kompier, Houtman, & Bongers, ; Sluiter, De Croon, Meijman, & Frings‐Dresen, ). Architectural solutions can help reduce speech intelligibility and the distractions caused by meaningful speech, but noise and its perception are also a function of social norms, institutional policies, and worker behavior (Oseland & Hodsman, ). The complex interplay of these functions points to the organizational importance of implementing a balanced solution for workplace privacy needs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, although we endeavoured to include a wider range of employee characteristics than had been typically considered in past research, it is nonetheless likely that additional unmeasured traits or characteristics also contribute to acoustic comfort and productivity in open-plan offices. For example, in Oseland and Hodsman's (2018) recent study, neuroticism (i.e. the tendency to experience negative emotions and experience anxiety and apprehension) had the largest effect on various noise metrics, particularly difficulties in concentration.…”
Section: Limitationsmentioning
confidence: 97%
“…Additionally, workplace management strategies could also help to improve acoustic comfort in open-plan offices by giving employees more control over their working environment. Indeed, the perception of control over noise has been identified as an effective way of reducing noise disturbance for all individuals, regardless of personality type (Oseland and Hodsman, 2018). One way to facilitate this would be through the clear demarcation of 'quiet zones' (and the enforcement of explicit rules governing the use of these spaces) combined with the implementation of an activity-based working policy would be effective in ensuring that occupants are able to choose a space which suits their current requirements (i.e., a space for silence or a space in which speech is encouraged and is not seen as distracting).…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Finally, although efforts were made to choose the most appropriate employee characteristics to measure on the basis of past research, it remains possible that a larger proportion of outcome variance would have been explained had additional characteristics been included. For example, in recent studies, the personality traits of neuroticism (Oseland and Hodsman, 2018) and the psychological need for privacy (Hoendervanger et al, 2018) were identified as important individual difference factors in the workplace. As research evolves, it will be necessary to hone in on those factors which are most strongly associated with workplace requirements, so that practitioners have greater clarity on what needs to be considered when providing workplace solutions.…”
Section: Limitationsmentioning
confidence: 99%